Diversity in orthopaedic surgery for pacific islanders: the battle continues - Ruan, Tiffany (International Journal of Research in Orthopaedics, 2023)
It’s no secret that orthopaedic surgery is the specialty with the least diversity when it comes to race and gender. More than likely, patients from different ethnic backgrounds desire to be treated by physicians ethnic backgrounds desire to be treated by physicians who look like them but due to the lack of diversity in the field of orthopaedic surgery, it makes it difficult to find physicians who fully understand the cultural barriers to medicine. A systemic review was completed by reviewing research from The American Journal of Surgery, the Journal of the AAOS, and The Journal of Bone and Joint Surgery, among others. Since the rapid immigration into the United States in the early 2000s, Pacific Islanders have begun to make up an increasing portion of the US population, yet a significant increase in the representation of Pacific Islanders in orthopaedic surgery has not reflected this. This acute problem can cause long-term negative effects on the community of Pacific islanders as they continue to be treated by physicians who do not look like them and who do not completely understand the cultural barriers faced by their communities.